The complete idiot's guide to Windows 95 - McFedries, Paul. 4 0 16; 5 (Indianapolis, IN : QUE, 1997)
A guide on how to use Windows 95, including how to install it; how to use the accessories; how to juggle files, folders, and programs; how to customize a workstation; how to connect to the Internet; and how to upgrade your Windows system.
Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; Microsoft Windows (Computer file);Microsoft Windows (Computer file); Windows (Computer programs).;Windows (Computer Software).; 20; 2